2011
DOI: 10.1021/ie200469e
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Free Nickel Micropillars Fabricated at a High Current Density by Application of a Supercritical Carbon Dioxide Emulsion

Abstract: Fast transport properties, extremely low surface tension, and nonpolar property of supercritical carbon dioxide (Sc-CO 2 ) are the key advantages of applying Sc-CO 2 in heterogeneous reaction like electroplating. Hydrogen gas bubbles have been found to be a cause of defects found in materials fabricated by electroplating. The physical limitation at the bottom of the photoresist patterns increases the difficulty for removal of hydrogen gas bubbles and diffusion of reactant species to the reaction site. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For example, our previous study demonstrated the application of sc-CO 2 emulsion baths in fabrication of void-free micro-patterns of nickel with improved growth rate [13]. Shinoda et al also reported that amount of the additive used in copper metallization of nano-scale holes could be reduced significantly by a sc-CO 2 suspension media [14].…”
Section: Introductionmentioning
confidence: 98%
“…For example, our previous study demonstrated the application of sc-CO 2 emulsion baths in fabrication of void-free micro-patterns of nickel with improved growth rate [13]. Shinoda et al also reported that amount of the additive used in copper metallization of nano-scale holes could be reduced significantly by a sc-CO 2 suspension media [14].…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, an alternative EP method employing a constant current density and a supercritical carbon dioxide (scCO 2 ) contained electrolyte was reported to be effective to give the grain refinement effect as demonstrated in electroplating of Ni and Cu [11,12]. Moreover, the specific properties of scCO 2 can promote transfer of materials into confined spaces and removal of H 2 gas bubbles away from the cathode, which allow application of high current density while keeping a defect-and pinhole-free plating at the same time [13][14][15]. In addition, co-deposition of carbon was reported in electroplating with an electrolyte containing scCO 2 at high pressure (EP-SCE) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…We have also developed a electroplating technique with supercritical carbon dioxide (sc-CO 2 ) [2,3]. Void-free micro-patterning is achieved by electroplating with sc-CO 2 [4,5]. High solubility and diffusivity of hydrogen in sc-CO 2 promote desorption and removal of hydrogen bubbles in the bottom/holes of the patterned structure.…”
Section: Introductionmentioning
confidence: 99%